Renewed: Protocol for a randomised controlled trial of a digital intervention to support quality of life in cancer survivors. Issue 3 (1st March 2019) - Krusche, Adele; Bradbury, Katherine; Corbett, Teresa; Barnett, Jane; Stuart, Beth; Yao, Guiqing Lily; Bacon, Roger; Böhning, Dankmar; Cheetham-Blake, Tara; Eccles, Diana; Foster, Claire; Geraghty, Adam William Alfred; et al.
Abstract : Introduction: Low quality of life is common in cancer survivors. Increasing physical activity, improving diet, supporting psychological well-being and weight loss can improve quality of life in several cancers and may limit relapse. The aim of the randomised controlled trial outlined in this protocol is to examine whether a digital intervention (Renewed), with or without human support, can improve quality of life in cancer survivors. Renewed provides support for increasing physical activity, managing difficult emotions, eating a healthier diet and weight management. Methods and analysis: A randomised controlled trial is being conducted comparing usual care, access to Renewed or access to Renewed with brief human support. Cancer survivors who have had colorectal, breast or prostate cancer will be identified and invited through general practice searches and mail-outs. Participants are asked to complete baseline measures immediately after screening and will then be randomised to a study group; this is all completed on the Renewed website. The primary outcome is quality of life measured by the European Organization for Research and Treatment of Cancer QLQ-c30. Secondary outcomes include anxiety and depression, fear of cancer recurrence, general well-being, enablement and items relating to costs for a health economics analysis. Process measures include perceptions of human support, intervention usage and satisfaction, and adherence to behavioural changes. Qualitative process evaluations will be conducted with patients and healthcare staff providing support. Ethics and dissemination: The trial has been approved by the NHS Research Ethics Committee (Reference 18/NW/0013). The results of this trial will be published in peer-reviewed journals and through conference presentations. Trial registration number: ISRCTN96374224 ; Pre-results.